2012
DOI: 10.1002/syn.21535
|View full text |Cite
|
Sign up to set email alerts
|

Affinity and selectivity of [11C]‐(+)‐PHNO for the D3 and D2 receptors in the rhesus monkey brain in vivo

Abstract: Although [¹¹C]-(+)-PHNO has enabled quantification of the dopamine-D3 receptor (D3R) in the human brain in vivo, its selectivity for the D3R is not sufficiently high to allow us to disregard its binding to the dopamine-D2 receptor (D2R). We quantified the affinity of [¹¹C]-(+)-PHNO for the D2R and D3R in the living primate brain. Two rhesus monkeys were examined on four occasions each, with [¹¹C]-(+)-PHNO administered in a bolus + infusion paradigm. Varying doses of unlabeled (+)-PHNO were coadministered on ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 68 publications
(92 reference statements)
0
62
2
Order By: Relevance
“…The injected mass of the radiotracer in our study slightly exceed the the mass limit suggested by Gallezot et al (2012), potentially leading to underestimation of dopamine occupancy in both conditions (Shotbolt et al, 2012). The injected mass, however, did not differ between the groups and did not correlate with [ 11 C]-( þ )-PHNO BP ND.…”
Section: (C) Expectancy Factor (Tobacco Craving Questionnaire Tcq)contrasting
confidence: 70%
“…The injected mass of the radiotracer in our study slightly exceed the the mass limit suggested by Gallezot et al (2012), potentially leading to underestimation of dopamine occupancy in both conditions (Shotbolt et al, 2012). The injected mass, however, did not differ between the groups and did not correlate with [ 11 C]-( þ )-PHNO BP ND.…”
Section: (C) Expectancy Factor (Tobacco Craving Questionnaire Tcq)contrasting
confidence: 70%
“…Fourth, baseline estimates of D 2 and D 3 binding were not 'true' baseline measures, as subjects were performing the cognitive (non-stressful) version of the MIST. Fifth, it has recently been suggested that [ 11 C]-( þ )-PHNO may not be at tracer dose in the D 3 -rich regions, which would hinder its accurate quantification (Gallezot et al, 2012;Rabiner and Laruelle, 2010). However, our significant findings were relatively specific to D 2 regions, and scan sessions (SMCT and MIST) were carried out on separate days, at least 5 days apart (except for one subject who could not come on two occasions).…”
Section: Resultsmentioning
confidence: 72%
“…[ 11 C](+)PHNO was prepared as previously reported (Gallezot et al, 2012). All PET scans were performed with the high-resolution research tomograph (Siemens/CTI, Knoxville, TN, USA), which acquired 207 slices separated by 1.2 mm with a reconstructed image resolution of~3 mm.…”
Section: Methodsmentioning
confidence: 99%